Preparation and characterization of polymer-coated mesoporous silica nanoparticles and their application in Subtilisin immobilization - Ozbek, Belma; Unal, Sule (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2017)
The preparation and characterization of polymer-coated mesoporous silica nanoparticles (MSNs) and their application in Subtilisin (AlcalaseA (R)) immobilization were investigated. For the synthesis of polymer-coated MSNs, acrylic acid (AA) and chitosan (CS) mixture were blended as poly(acrylic acid) (PAA) and CS polymer layer onto MSNs via in-situ polymerization technique. Then, both uncoated MSNs and polymer-coated mesoporous silica nanoparticles (CS-PAA/MSNs) were characterized by taking into account properties such as morphologic pattern, size distribution, surface charge of the particles as well as thermogravimetric stability with SEM, TEM, Zetasizer and TGA analyses. Subtilisin was immobilized onto polymer-coated mesoporous silica nanoparticles via adsorption technique. For optimizing the enzyme immobilization process, the percent enzyme loading depending on the matrix amount, immobilization time and pH were investigated. Then, the activity values of immobilized enzyme and free enzyme were compared at various pH and temperature values. The maximum enzyme activity was achieved at pH 9.0 for both immobilized and free enzyme. Immobilized enzyme showed more stability at higher temperatures compared with free enzyme. Furthermore, the operational and storage stability of immobilized enzyme were determined. The activity of immobilized enzyme was reduced from 100% to 45.83% after five repeated uses. The storage stability of immobilized enzyme was found to be higher than that of free enzyme. The activity of immobilized enzyme was reduced from 100% to 60% after 28 days of storage time. We concluded that the polymer-coated MSNs were a suitable matrix for Subtilisin immobilization compared to uncoated MSNs.
Keywords: Nanobiocatalysis; Silica Nanoparticles; Chitosan; Poly(acrylic) Acid; Enzyme Immobilization; Subtilisin; Optimal Conditions; DRUG-DELIVERY; PROTEASE; ADSORPTION; Chemistry; Engineering